2004
DOI: 10.1177/0092070303257646
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Contingency Awareness, Involvement and Need for Cognition in Attitude Formation

Abstract: This research investigates the role of involvement and need for cognition in influencing contingency awareness in attitude formation. Two experiments examine the nature of favorable attitudes formulated through established classical conditioning procedures. The results of Experiment 1 indicate that awareness influences attitudes toward a conditioned stimulus, particularly under conditions of high involvement and high need for cognition. Experiment 2 suggests that contingency awareness mediates the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…Low involvement means that behaviour does not necessarily reflect attitudes or knowledge (Chaffee & Roser 1986;Priluck & Till 2004). However, if there is a need for farmers to use nutrient budgets more effectively*that is, a need for farmers to respond to the outcomes of their budget and change the way in which they manage parts of their farm*these results indicate that there is a need to increase the level of involvement in nutrient budgeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low involvement means that behaviour does not necessarily reflect attitudes or knowledge (Chaffee & Roser 1986;Priluck & Till 2004). However, if there is a need for farmers to use nutrient budgets more effectively*that is, a need for farmers to respond to the outcomes of their budget and change the way in which they manage parts of their farm*these results indicate that there is a need to increase the level of involvement in nutrient budgeting.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of an issue or problem, involvement in that issue or problem and the need to think through a problem or issue are all required for attitude formation (Priluck & Till 2004). To illustrate, in evaluating a communication campaign designed to increase recycling, Larson & MassettiMiller (1984) found that although there was no change in recycling behaviour there were attitude changes, but only amongst those people who already recycled (i.e.…”
Section: Involvementmentioning
confidence: 99%
“…Along with this theory, humor can serve as a peripheral cue to persuasion and stimulate delayed responses to brands (including attitudes). However, as noted by Petty and Cacioppo 27 and Petty et al 28 , these responses are less persistent over time and less predictive of behavior than attitudes triggered by the central route.…”
Section: Prank Effects On Brands -Implications From Theory Of Hu-mormentioning
confidence: 88%
“…In advertising, the effects of attitude conditioning have been proven in different contexts. A product associated with a pleasant piece of music is evaluated higher than one associated with disagreeable music [43], The effects of evaluative conditioning are stronger in forming attitudes (the case of new brands) than in changing already established ones (the case of familiar brands) [44]. In this latter case, some research studies did not manage to change attitudes [45], while others registered some small-scale changes [46].…”
Section: Attitude Conditioning Produces Effects On Implicit Attitudesmentioning
confidence: 99%